DAMPAK GREENPEACE MENGKAMPANYEKAN DETOX MY FASHION TERHADAP PENCEMARAN LINGKUNGAN DI CHINA - Anjani, Rezalis; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research is about the impact of Greenpeace's Detox My Fashion campaign on environmental pollution in China. In 2011, Greenpeace launched the Detox My Fashion campaign because two large factories in China, namely Youngor and Well Dyeing, dumped hazardous chemical waste into the Yangtze and Pearl rivers. This research uses Global Civil Society theory and the group level of analysis to examine the changes created by Greenpeace. Global Civil Society theory is a form of international communication which is interpreted as voluntary activities carried out by Greenpeace with the aim of forming policies, norms or social structures that can be distinguished commercially or politically. The results of this research show that the impact of the Detox My Fashion campaign in China is that fashion brands are able to reduce the use of dangerous chemicals in the clothing production process. The impact of fast fashion is so bad that China issued the Yangtze Rivers Protection Law to protect the Yangtze River from environmental pollution. Keywords: Greenpeace, Fast Fashion, Campaign Detox My Fashion, China